Application of advanced materials for enhancing the fire performance of slim‐floors. (13th September 2017) - Espinós, Ana; Albero, Vicente; Romero, Manuel L.; Hospitaler, Antonio; Ibáñez, Carmen
ABSTRACT: Composite steel‐concrete beams embedded in floors (slim‐floors) are increasingly used in new construction proposals for residential, industrial and commercial floors, which motivates the need for assessing their fire behaviour. However, EN 1994‐1‐2 does not provide simplified methods to obtain the temperature distribution in the cross‐section, which is available for other types of composite solutions such as partially encased composite beams. As a consequence, this paper presents an advanced finite element thermal model to evaluate the temperature distribution in slim‐floors, calibrated against tests from bibliography, specifically for commercially available slim‐floor configurations such as Shallow Floor Beams (SFB). This thermal model will help to assess the fire behaviour of slim‐floors. Additionally, the usage of advanced materials such as High Strength Steel (HSS), and lightweight concrete for slim‐floors is evaluated through the developed finite element thermal model, in order to provide design recommendations on the most favourable configurations. This paper presents a first approach to evaluate the benefits of the application of these innovative materials to slim‐floors.